2017
DOI: 10.1111/anae.14179
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre‐operative gastric ultrasound examination on the choice of general anaesthetic induction technique for non‐elective paediatric surgery. A prospective cohort study

Abstract: Ultrasound examination of the gastric antrum is a non-invasive tool that allows reliable estimation of gastric contents. We performed this prospective cohort study in non-elective paediatric surgery to assess whether gastric ultrasound may help to determine the best anaesthetic induction technique, whether rapid sequence or routine. The primary outcome was the reduction of inappropriate induction technique. A pre-operative clinical assessment was performed by the attending anaesthetist who made a provisional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 31 publications
2
66
1
3
Order By: Relevance
“…Thus, the combination of the data of five studies using a three‐position blind aspiration technique to assess the gastric fluid volume in a total of 611 elective children found that the mean ± SD gastric fluid volume was 0.4 ± 0.45 mL/kg, and was <1.25 mL/kg in 95% of these children . Conversely, we recently reported that 66/143 (46%) of children undergoing urgent or emergency surgery had increased gastric contents volume as assessed by nasogastric aspiration . In the current study, the prevalence of gastric fluid volume >1.25 mL/kg ranged from 0.2%‐3.9% and was significantly lower than that of a gastric fluid volume >0.8 and >1 mL/kg.…”
Section: Discussioncontrasting
confidence: 45%
“…Thus, the combination of the data of five studies using a three‐position blind aspiration technique to assess the gastric fluid volume in a total of 611 elective children found that the mean ± SD gastric fluid volume was 0.4 ± 0.45 mL/kg, and was <1.25 mL/kg in 95% of these children . Conversely, we recently reported that 66/143 (46%) of children undergoing urgent or emergency surgery had increased gastric contents volume as assessed by nasogastric aspiration . In the current study, the prevalence of gastric fluid volume >1.25 mL/kg ranged from 0.2%‐3.9% and was significantly lower than that of a gastric fluid volume >0.8 and >1 mL/kg.…”
Section: Discussioncontrasting
confidence: 45%
“…Gastric ultrasound resulted in the appropriate use of the indicated induction technique (RSI vs routine induction) in 85% of patients. The planned induction technique based on clinical assessment alone was consistent with postintubation findings following gastric suctioning (ie, RSI performed and gastric contents evacuated) in only 49% of patients . Further studies are needed to develop risk estimates for patients with radiographic evidence of residual gastric contents, such as high‐risk neonates or patients with difficult airways where it could be argued that the immediate risk of hypoxemia from strictly withholding ventilation may be greater than that of aspiration, as well as demonstrate actual risk reduction for pulmonary aspiration, which will be challenging, given aspiration is, fortunately, an infrequent event.…”
Section: Oxygen Deliverymentioning
confidence: 95%
“…The recent introduction of point‐of‐care gastric ultrasound has rekindled the interest and discussion adding new perspectives and fresh human data to our understanding . There has been a burst of new publications recently, including two in this issue of Anaesthesia . Ultrasound studies confirm that gastric volumes of up to 1.5 ml.kg −1 are normal in healthy fasted individuals with baseline risk.…”
Section: Assessmentmentioning
confidence: 99%